Vertical Green Landscape Facades as a Reducer of Pollution in HighDensity Cities: A Review - Hamling, Anna; Van Dam, Caitlyn; Dubbeldee, Victoria (Urban Planning and Construction, 2024)
As urbanization continues to intensify, high-density cities grapple with escalating environmental and social challenges that directly impact the well-being of their inhabitants. This paper explores the potential of vertical green landscape facades as a pragmatic solution to mitigate these issues while fostering sustainability within urban environments. In recent times, vertical green landscape design concepts have garnered increasing attention and popularity for their ability to combat pollution and enhance the quality of life in densely populated urban areas. This paper delves into the manifold benefits of vertical green landscapes, as demonstrated by recent research, focusing on their positive reception among the public and their capacity to offer novel avenues for developing green infrastructure. Through an in-depth analysis of relevant literature and case studies, this paper evaluates the role of vertical green landscapes as an effective reducer of pollution in high-density cities. It discusses their capacity to mitigate air and noise pollution, improve microclimates, and contribute to urban aesthetics. Additionally, it addresses the social and psychological advantages of integrating these green systems into urban design, emphasizing their potential to enhance the well-being and livability of city dwellers. By combining quantitative and qualitative methods, the study aims to provide a holistic understanding of the benefits and challenges associated with these innovative urban green solutions. In conclusion, this paper underscores the pivotal role of vertical green landscape facades as a sustainable and aesthetically pleasing means of combatting the environmental and social challenges of high-density urbanization. By presenting empirical evidence of their efficacy and positive reception, it advocates for their increased integration into urban planning and design strategies as a pragmatic response to the complex issues faced by contemporary cities.